Bambara groundnut ameliorates kidney histology in female mice with protein deficiency - Firdiana, Vykra Aulia; Gunanegara, Rimonta Febby; Sunarti; Nuriliani, Ardaning (Medical Journal of Indonesia, 2023)
BACKGROUND Protein deficiency (PD) can lead to kidney damage. Consuming plant-based proteins may improve this condition. Bambara groundnut (Vigna subterranea)has an essential amino acid score of 80%, which is higher than other legumes; thus, it is potent in overcoming malnutrition. This study aimed to determine the effect of Bambara groundnut supplementation on kidney histology in adult female mice with PD. METHODS The study was conducted for 2 months in randomly selected female mice. These mice were grouped into the control, PD, and PD supplemented with Bambara groundnuts at 100, 200, and 300 g/kg of feed. 1 day after the last treatment, the kidneys of the mice were collected and processed histologically using the paraffin method (stained with hematoxylin and eosin and Masson’s trichrome). Parameters for observation included histopathological scoring (glomerular and interstitial space fibrosis and tubular damage), kidney histomorphometry, and organ index. Semi-quantitative data were analyzed using the Kruskal–Wallis test, while quantitative data were analyzed using one-way ANOVA (followed by Tukey’s test) and nested t-test. Statistical analysis was performed using SPSS software version 20 (IBM Corp., USA) (p≤0.05). RESULTS PD caused cell sloughing (moderate level) and dilatation (severe level) of the kidney tubules. It also reduced glomerular diameter and area by approximately 17.66% and 29%, respectively. PD and Bambara groundnut administration had no significant effects on the glomerular number, cortex and medulla thickness, distal and proximal tubule diameter, and kidney organ index (p>0.05). CONCLUSIONS Bambara groundnut (V. subterranea) administration prevented damage to the kidney’s histological structure of protein-deficient mice.